2022
DOI: 10.1021/acsami.1c22983
|View full text |Cite
|
Sign up to set email alerts
|

Designing Monoclinic Heterophase Coexistence for the Enhanced Piezoelectric Performance in Ternary Lead-Based Relaxor Ferroelectrics

Abstract: Enhanced piezoelectric, dielectric properties and thermal stability in ternary relaxor-PbTiO 3 based ferroelectric crystals are expected to develop the next-generation of electromechanical devices. However, due to their increased disorder compared to other ferroelectrics, designing a controllable phase boundary structure and engineered domain remains a challenging task. Here, we construct a monoclinic heterophase coexisting in a ternary Pb(In 1/2 Nb 1/2 )O 3 −Pb(Mg 1/3 Nb 2/3 )O 3 −PbTiO 3 single crystal with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Raman spectroscopy has been successfully used in electroceramics also for spatially resolved phase analyses, such as polytype detection in SiC 97,98 , solid solution studies in AlN-SiC composites 99 , and the determination of heterophase mixtures in the relaxor ferroelectric Pb(In 1/2 Nb 1/2 )O 3 -Pb(Mg 1/3 Nb 2/3 )O 3 -PbTiO 3 100 . Quantitative analyses of phase segregation, similar to the determination of monoclinic fraction in zirconia ceramics 101,102 , however, require the presence of suitable standards with a known phase fraction 103 .…”
Section: Application To Electroceramicsmentioning
confidence: 99%
“…Raman spectroscopy has been successfully used in electroceramics also for spatially resolved phase analyses, such as polytype detection in SiC 97,98 , solid solution studies in AlN-SiC composites 99 , and the determination of heterophase mixtures in the relaxor ferroelectric Pb(In 1/2 Nb 1/2 )O 3 -Pb(Mg 1/3 Nb 2/3 )O 3 -PbTiO 3 100 . Quantitative analyses of phase segregation, similar to the determination of monoclinic fraction in zirconia ceramics 101,102 , however, require the presence of suitable standards with a known phase fraction 103 .…”
Section: Application To Electroceramicsmentioning
confidence: 99%
“…Under adiabatic conditions, the phase transition of the low-temperature R phase to the high-temperature T phase induced by a non-collinear electric field can produce a negative EC peak [25], while the T-C phase transition can produce a positive EC peak. However, some researchers who focus on the piezoelectric properties of the relaxor ferroelectric single crystal have found that there was an intermediate monoclinic (M) phase during the R-T phase transition [26][27][28][29]. If this is the case, the traditionally considered R-T phase transition process will be divided into three parts, namely, R-M phase transition, single ferroelectric M phase transition, and M-T phase transition.…”
Section: Introductionmentioning
confidence: 99%
“…16 In addition, Cui et al obtained PIN-PMN-PT crystals with giant piezoelectric properties of 1400 pC/N and a high Curie point of 200 °C, while the crystals are opaque. 17 Thus, the PIN-PMN-PT system is possible to obtain high piezoelectric properties, high Curie temperature, and high transmittance simultaneously. However, few researchers have focused on PIN-PMN-PT transparent piezoelectric ceramics.…”
Section: Introductionmentioning
confidence: 99%
“…In 2022, Li and co-workers successfully fabricated Pb­(In 1/2 Nb 1/2 )­O 3 -Pb­(Mg 1/3 Nb 2/3 )­O 3 -PbTiO 3 (PIN-PMN-PT) crystals with an ultra-high transmittance of 70% and high Curie point of 180 °C, while the piezoelectric properties were relatively low . In addition, Cui et al obtained PIN-PMN-PT crystals with giant piezoelectric properties of 1400 pC/N and a high Curie point of 200 °C, while the crystals are opaque . Thus, the PIN-PMN-PT system is possible to obtain high piezoelectric properties, high Curie temperature, and high transmittance simultaneously.…”
Section: Introductionmentioning
confidence: 99%